If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(1/3)*(6*x+9) = 0
1/3*(6*x+9) = 0
6*x+9 = 0 // - 9
6*x = -9 // : 6
x = -9/6
x = -3/2
x = -3/2
| 5x+10+6x+3=90 | | -4(2f-4)=-4(-f+2) | | x+0.000005ln(x)=-0.0000316 | | 6d= | | 1/2(a+5)=7.5 | | h(t)=40t-5t^2 | | -4y-9/-3 | | x+2+4x-12=90 | | -(2a+6)=2(3a+8) | | 16x+9=8x+38 | | 15x-10/5 | | d-7=15 | | (5x+8)(3x-9)= | | 0m= | | 15m= | | 5s=s+5+s | | 10b-3=6b-5+2b | | 4x+32=8x+8 | | 2(h+3)=6(h-3) | | x-3/8=-5/8 | | 4y+2=94 | | q-12-13= | | 1/7(2k-3)=-5 | | 4p=p+3.6 | | 22p+12=4p-7 | | x+.5=.75 | | .06*.12=4920 | | 6x^2+5x-9=0 | | -4+2(y+3)=-3y-26 | | 2460+2460= | | ln(x+8)=2 | | 16x+12=8x+45 |